2020
DOI: 10.1002/ldr.3537
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year soil moisture response of typical cultivated grasslands in a semiarid area: Implications for vegetation restoration

Abstract: Soil water deficit is one of the important abiotic stresses affecting vegetation restoration.The magnitude and spatiotemporal dynamics of soil water content (SWC) provide basic guidance for optimal vegetation restoration. In a semiarid Chinese area, the changes in the soil water storage (SWS) of five cultivated grasslands and one wasteland were observed, to evaluate the water consumption at different soil depths (0-100 cm), from 2008 to 2012. The plants of the three leguminous species consumed more water in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Previous studies confirmed that the ability of different vegetation restoration types to improve soil quality are different (Yu et al, 2018;Dang et al, 2020;Liu et al, 2020). In this study, the effect on soil quality (0-30 cm) of natural shrubland was significantly higher than that of Eucalyptus robusta, Prunus salicina and Juglans regia-crop (Fig.…”
Section: Analysis Of the Effects Of Different Vegetation Restoration supporting
confidence: 81%
“…Previous studies confirmed that the ability of different vegetation restoration types to improve soil quality are different (Yu et al, 2018;Dang et al, 2020;Liu et al, 2020). In this study, the effect on soil quality (0-30 cm) of natural shrubland was significantly higher than that of Eucalyptus robusta, Prunus salicina and Juglans regia-crop (Fig.…”
Section: Analysis Of the Effects Of Different Vegetation Restoration supporting
confidence: 81%
“…Changes in land use and cover with respect to preexisting natural grasslands can alter plant community composition and soil characteristics (Dang et al, 2019; Huang et al, 2018; Merbold et al, 2014). These alterations can, in turn, affect soil microbial communities (Du et al, 2019; Qi et al, 2017; Yokobe et al, 2020) and their attendant biogeochemical cycles (Kaushal et al, 2014; Pataki et al, 2011; Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies such as those by Ngo-Mbogba [61] have shown that the SQIs of various vegetation sorts are considerably different. Some recent studies have additionally confirmed that different vegetation restoration types have different abilities to enhance soil quality [79,80].…”
Section: Soil Quality Indexmentioning
confidence: 90%